Principal-Agent Relation in Conserving the Kali Putih Area in the Reconstruction and Mitigation Zone of Merapi Mountain National Park - Ammy Nurwati; Bevaola Kusumasari; Agus Pramusinto; Ahmad Maryudi (Indonesian Association for Public Administration, 2020)
This article aims to observe the dynamics of policy implementation involving various stakeholders in the effort of conserving one of the National Parks in Indonesia, particularly Merapi Mountain National Park (Taman Nasional Gunung Merapi – TNGM). Following the Zoning Policy implemented in the TNGM area, there is a zone that should have been protected from mining activities, namely the reconstruction and mitigation zone. However, in its implementation, the conservation collaboration agreement of one of the areas in the zone, namely the Kali Putih Area, is instead used by some parties to engage in sand mining activities. The principal-agent theory is, thus, employed in this study to examine the extent of the relationship of every party in the zoning policy implementation process of an area designated as a Reconstruction and Mitigation Zone. The qualitative approach is used to gain direct insights pertaining to the implementation of efforts conducted by several relevant parties in conserving the Kali Putih Area in TNGM’s Reconstruction and Mitigation Zone. Study results ultimately show that moral hazard in the principal-agent theory should not only be understood as deviant behaviors enacted by the agent, but the moral hazard performed by the agent may also inϐluence the principal’s decision making process. This research is expected to provide an outlook to the government, which functions as the principal in a policy, to make several considerations prior to entering into any collaborative agreement or making any decision, so that the implementation process of policies can align with what has been previously planned.